Fatal Case of Acute Pulmonary Embolism due to Venous Thrombosis after COVID-19 Vaccination: Based on Forensic Postmortem Examination - Park, Sohyung; Won, Yujin; Lee, Sookyoung (Korean Journal of Legal Medicine, 2021)
We present an unexpected fatal case of pulmonary embolism due to venous thrombosis after vaccination for coronavirus disease 2019 (ChAdOx1 nCov19). The deceased was a 64-year-old woman with Alzheimer disease. The deceased had fever shortly after vaccination, and presented sudden dyspnea and died 8 days after vaccination. On postmortem examination, pulmonary embolism and venous thrombosis were noted in deep veins of both lower legs. Even though the psychomotor function of the deceased became fragile due to Alzheimer disease, the deceased was not bed-ridden, and major known risk factors related to venous thrombosis were not explicit in this case. Because there are not enough data related to vaccination and thrombosis, we hope that this case would be helpful in unraveling pathogenesis of venous thrombosis after vaccination and in determining whether there is any association between thrombosis and vaccination. KCI Citation Count: 0